Uma introdução às equações funcionais - Bezerra, Alex Pereira (2014)
This paper presents a study on functional equations, considering its relevance to the teaching of mathematics, with the ultimate goal of presenting a proposal to contribute to the improvement of teaching this topic. A summary of the history of functional equations is presented. Then, Chapter 1 consists of the study of the Cauchy Functional Equations, Chapter 2 deals with equations Jensen, Pexider, d 'Alembert. In chapter 3 we show some applications of functional equations.